Suaveolic Acid: A Potent Phytotoxic Substance of Hyptis suaveolens - A. K. M. Mominul Islam; Osamu Ohno; Kiyotake Suenaga; Hisashi Kato-Noguchi (The Scientific World Journal)
Hyptis suaveolens (Lamiaceae) is an exotic invasive plant in many countries. Earlier studies reported that the aqueous, methanol, and aqueous methanol extract of H. suaveolens and its residues have phytotoxic properties. However, to date, the phytotoxic substances of this plant have not been reported. Therefore, the objectives of this study were isolation and identification of phytotoxic substances of H. suaveolens. Aqueous methanol extract of this plant was purified by several chromatographic runs through bioassay guided fractionation using garden cress (Lepidium sativum) as a test plant. Final purification of a phytotoxic substance was achieved by reverse phase HPLC and characterized as 14α-hydroxy-13β-abiet-8-en-18-oic acid (suaveolic acid) by high-resolution ESI-MS, 1H-,13C-NMR, CD, and specific rotation. Suaveolic acid inhibited the shoot growth of garden cress, lettuce (Lactuca sativa), Italian ryegrass (Lolium multiflorum), and barnyard grass (Echinochloa crus-galli) at concentrations greater than 30 µM. Root growth of all but lettuce was also inhibited at concentrations greater than 30 µM. The inhibitory activities were concentration dependent. Concentrations required for 50% growth inhibition of suaveolic acid for those test plant species were ranged from 76 to 1155 µM. Therefore, suaveolic acid is phytotoxic and may be responsible for the phytotoxicity of H. suaveolens plant extracts.